Great Mining Camps of Canada 3. The History and Geology of the Buchans Mine, Newfoundland and Labrador - Thurlow, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY The 1905 mineral discovery at Buchans River resulted from efforts by the Anglo-Newfoundland Development Company Lim ited (AND) to establish a pulp and paper industry in central Newfoundland. The discovery is attributed to Matty Mitchell, a legendary Mi’kmaq guide, who was employed by AND to assist William Canning in prospecting for sulphur on company leasehold land. The company explored the prospect and developed a small deposit, under the supervision of William Scott; however, early attempts to create a producing mine were frustrated by metallurgical difficulties and ended in 1911. Harry Guess, a director of the American Smelting and Refining Company Incorporated, (later ASARCO) had heard about the discovery, and in 1916 contacted William Scott. ASARCO conducted extensive research on samples of Buchans ore, and by 1925 had developed a successful metallurgical method of separating the fine-grained zinc, lead and copper minerals. In 1926, ASARCO entered into a 25-year agreement with AND and its subsidiary, Terra Nova Properties, to develop Buchans; Guess also made the decision to hire pioneer Swedish geo-physicist Hans Lundberg to conduct electrical prospecting on the property. In June and July of that year, Lundberg used his new geophysical technique to discover the Lucky Strike and Oriental orebodies. They would ultimately prove to be the first discoveries in North America attributed to the emerging science of electromagnetic prospecting. A production shaft was collared at Lucky Strike in 1926 and under the supervision of J. Ward Williams, construction began the following year on a 450 tonne per day mill as well as the townsite, railroad, hydroelectric plant and other facilities. The complex began production in September 1928 and by the end of 1929, ore reserves were approximately 5.6 million tonnes. The mill was enlarged to 1100 tonnes per day in 1931; by the end of 1947, ore reserves had declined to 1.4 million tonnes. However, renewed exploration resulted in two discoveries in 1947 and 1950, named the Rothermere and MacLean orebodies, respectively. The Buchans orebodies are part of the Middle Ordovician Buchans Group, which comprises an allochthonous sequence of bimodal, submarine volcanic rocks that were deposited in the Iapetus Ocean near the margin of Laurentia. These ore-bodies are classified as volcanogenic massive sulphide (VMS) deposits and are among the highest-grade examples of this class worldwide. From 1928 to 1984, ASARCO mined approximately 16 million tonnes from five orebodies, with an average mill head grade of 14.51% zinc, 7.56% lead, 1.33% copper, 126 g/t silver and 1.37 g/t gold. Apart from their high grade, these deposits are remarkable for the extensive development of debris-flow ores, which provided important evidence for seafloor deposition of VMS deposits in an era when this concept was not widely accepted.